Analysis of economic impact from erosive wear by hard particles in a run-of-the-river hydroelectric plant. (15th October 2016) - Teran, L.A.; Aponte, R.D.; Muñoz-Cubillos, J.; Roa, C.V.; Coronado, J.J.; Ladino, J.A.; Larrahondo, F.J.; Rodríguez, S.A.
Abstract: Small-scale hydroelectric plants, primarily run-of-the-river designs, are regularly subjected to hard particle wear and cavitation erosion due to the wide range of operating points. Depending on the severity of the operating conditions and erosion damage experienced by the machine throughout its service life, the operating companies of these facilities will be impacted. The impact will be technical, operational, logistical, and economic. A small-scale generation plant located in Amaime River in Colombia, is one such case, where severe wear occurs in the turbine components, with a consequent reduction of efficiency. In this study, the analysis of the erosion damage has been expanded and supplemented by computational fluid dynamics (CFD). From this approach, correlations between the wear rate and power output were obtained. Likewise and in conjunction with the computer estimates, a methodology to analyse the costs associated with wear based on historical data of operation was developed, creating a strategy of operation based on a stopping criterion that depends primarily on sediment concentration, turbinated flow, and wear level. The methodology optimizes the use of generators, which takes into consideration the revenue generation and the costs associated with operation and maintenance of pieces under conditions of intrinsic erosion wear in the facility. Highlights: CFD and wear analysis are combined to improve the operation of a Francis turbine. Correlations between the wear rate and power output were obtained. The costs associated with wear based on historical data of operation were obtained. A new strategy of operation based on a stopping criterion was developed. The stopping criterion depends of sediment concentration, flow, and cost in kW-h.